2023
DOI: 10.3390/ma16155224
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Assessment of Zinc Alloys as a New Potential Material for Bioabsorbable Implants for Osteosynthesis

Maria Roesner,
Sergej Zankovic,
Adalbert Kovacs
et al.

Abstract: In the last several years, zinc and its alloys have come into focus as bioabsorbable materials by qualifying themselves with an excellent corrosion rate, mechanical properties, anti-bacterial effects. and considerable biocompatibility. In this study, the biocompatibility of zinc–silver alloys containing 3.3 wt% silver (ZnAg3) was assessed by evaluating their cell viability, the proliferation rate, and the cell toxicity. Two alloys were investigated in which one was phosphated and the other was non-phosphated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Hagelstein et al [38] described a corrosion rate of 0.14 mm/year for ZnAg3 with an Ag content of 3.0 wt% manufactured by Limedion and Quadralux (Limedion GmbH, Mannheim, Germany; Quadralux e.K., Mannheim, Germany), which is slightly higher than the measured corrosion rate in this study. This circumstance might be due to the fact that the grain size of the ZnAg3 in this study was determined to be smaller at 5-10 µm and the Ag content was higher at 3.3 wt%, as previous investigations could show [47]. Thus, it is apparent that the grain size in fact impacts the corrosion rate.…”
Section: Electrochemical Measurementsmentioning
confidence: 50%
See 3 more Smart Citations
“…Hagelstein et al [38] described a corrosion rate of 0.14 mm/year for ZnAg3 with an Ag content of 3.0 wt% manufactured by Limedion and Quadralux (Limedion GmbH, Mannheim, Germany; Quadralux e.K., Mannheim, Germany), which is slightly higher than the measured corrosion rate in this study. This circumstance might be due to the fact that the grain size of the ZnAg3 in this study was determined to be smaller at 5-10 µm and the Ag content was higher at 3.3 wt%, as previous investigations could show [47]. Thus, it is apparent that the grain size in fact impacts the corrosion rate.…”
Section: Electrochemical Measurementsmentioning
confidence: 50%
“…Therefore, the extrusion process and the associated effects on grain size have an impact on the material properties. In this study, ZnAg3 manufactured by Limedion and Quadralux (Limedion GmbH, Mannheim, Germany; Quadralux e.K., Mannheim, Germany) showed a grain size of 5-10 µm after hot extrusion at 250-300 °C with an extrusion rate of 25:1 [47]. In comparison, Sikora-Jasinska et al [30] reported a UTS of 203 MPa, a YS of 157 MPa, and an elongation at fracture of approximately 34% for ZnAg2.5 with a grain size of 16 µm after hot extrusion at 250 °C with an extrusion rate of 14:1.…”
Section: Mechanical Measurementsmentioning
confidence: 76%
See 2 more Smart Citations